Penerapan Strategi Problem Based Learning dalam Meningkatkan Kemampuan Siswa pada Mata Pelajaran Al-Qur’an Hadits - Arina Arina; Rizky Nanda Arleni; Afifah Salsabila; Rasyidi Sinambela; May Saroh (Departement of Mathematics Education, 2023)
The Qur'an Hadits is one of the subjects of Islamic Religious Education in schools. This study aims to find out what strategies teachers use and find out what factors are obstacles in implementing these learning strategies. This research uses a qualitative research approach. Qualitative research is systematic research that is used to study or examine an object in a natural setting without any manipulation in it and without any hypothesis test. The results showed that Problem Based Learning learning, educators only act as facilitators and as motivators. Educators motivate learners to actively engage in the search for problem-solving solutions. Educators help and guide learners to utilize relevant resources and help learners to be able to interact and collaborate in groups to provide the best alternative solutions.